Does a Single Bout of Low-Intensity Resistance Exercise Change Baroreflex Sensitivity? (International Journal of Physiotherapy, 2021)
Background: Baroreflex sensitivity (BRS) has decreased in patients with hypertension, diabetes mellitus, and congestive heart failure. According to ATRAMI (Autonomic Tone and Reflex After Myocardial Infarction), BRS is helpful for the prediction of the sudden death of persons who have experienced myocardial infarction.Methods: Twenty-four sedentary healthy men with a mean age of 21.0 years, mean body mass of 62.5kg, mean height of 171.1cm, and a body mass index of 21.3kg/m2.Procedure: In a single session, the participants performed a total of 20 alternating knee extensions in sitting with each excursion consisting of a five-second contraction and five-second rest period with a 20% load of one-repetition maximum. Autonomic nerve activity and BRS were measured during LRE using impedance cardiography and hemodynamic parameters for cardiac function. In addition, a continuous R-R series was taken of the heart rate with quantification of spectral powers for regions of high frequency (HF) and low frequency (LF). Also calculated were LF/ HF of the R-R interval variability power ratio and the HF normalized unit (HFnu) as indicators for sympathetic and parasympathetic nerve activity.Results: There was a significant decrease in LF/HF post-LRT (P=0.045) with a significant increase in HFnu and BRS (P=0.01 and P=0.032, respectively).Conclusion: A single bout of LRE proved to enhance BRS function in healthy men.